Determination of trace levels of uranium in waste solutions by energy dispersive X‐ray fluorescence following adsorption on graphene oxide. (9th August 2022) - Yoshii, Hiroshi; Uwatoko, Tetsuaki; Takahashi, Hiroaki; Sakai, Yasuhiro
Abstract: This paper proposes a rapid X‐ray fluorescence (XRF)‐based screening method for the determination of trace uranium in solutions. In this method, uranium present in a solution was adsorbed onto graphene oxide (GO), which was collected and subjected to XRF analysis. Upon increasing the sodium ion concentration, the aggregation of GO was promoted, facilitating its collection. Since the GO‐collecting membrane filter was significantly larger than the X‐ray irradiation field of the XRF spectrometer, it was folded to 1/3 of its original length and width. The folded membrane filter was sealed to prevent uranium from contaminating the device and to ensure that the folded membrane filter was sufficiently thin. Subsequently, the amount of sodium perchlorate added to the sample solution was optimized to attain a salinity meter reading of 3%. The minimum detection limit (MDL) for uranium using this method was 0.37 ng ml −1, and the time required to simultaneously analyze six samples was approximately 2 h. Converting the MDL to the radioactivity concentration under conservative conditions generated a value of 0.037 mBq cm −3 . To demonstrate the applicability of this method, a standard seawater sample was subjected to analysis, and the uranium concentration determined using our calibration curve agreed with the actual value within a margin of error. Therefore, the proposed method is suitable for screening numerous uranium‐contaminated water samples of small volumes.